Soft Semi Totally Continuity in Soft Topological Spaces - Sabih Askandar (College of Education for Pure Sciences, 2023)
The soft semi-totally continuous mappings that we have introduced in this study are stronger than the soft totally continuous mappings and provide fresh thoughts for soft continuous mappings between several soft topological spaces. By using evidence and guidelines to clarify and explain it, the relationships between these notions and several other concepts of soft mappings have been studied. Also, several of these functions' characteristics have been looked into. Moreover, soft semi-totally open mappings have been shown and investigated. Additionally, we defined soft continuous mappings that depend on soft i-open sets and looked at how they are related to soft continuous mappings that depend on soft semi-open sets. In this paper we proved that each soft semi-totally continuous mapping is soft totally continuous , each soft strongly semi continuous mapping is soft strongly i-continuous, each soft totally semi continuous mapping is soft totally i-continuous, the composition of two soft semi totally open mappings is soft semi totally open mapping, and the composition of two soft semi totally continuous mappings is soft semi totally continuous mapping.